Study on Failure Characteristics and Rock Burst Mechanism of Roadway Roof under Cyclic Dynamic Load. (14th December 2021) - Zheng, Chunmei; Zheng, Jiayan; Peng, Xiaojuan; Zhou, Lei
Abstract : Rock burst is a catastrophic phenomenon that often occurs in underground rock mass engineering. In order to reveal the essence of rock burst of a hard roof in the process of roadway excavation, the particle discrete element method is used to establish a roadway model and simulate the disturbance of harmonic dynamic load based on the analysis of a rock burst accident in a deep mine. The crack field, stress field, displacement field, and kinetic energy of roadway surrounding rock disturbed by cyclic dynamic load were analyzed, and the disaster mechanism of roadway impacting roof instability was discussed. The results show that, compared with the roadway support structure under static load that can give full play to its control function of surrounding rock, the roadway surrounding rock will collapse and lose stability in a large area under the roof cyclic dynamic load, and the ordinary supporting structure cannot give full play to its control function of surrounding rock, resulting in the surrounding rock destruction and supporting structure failure. In addition, the essence of rock burst in a hard thick roof is due to the instantaneous superposition of static stress and dynamic load, leading to the instantaneous instability and collapse of roadway roof in a large area. The research is of great significance to further understand the deformation and failure mechanism of roadway surrounding rock under strong impact load, to guide the safe production and prevent the occurrence of rock burst hazard in underground rock mass engineering.